IDENTIFIKASI KESALAHAN SISWA MEMAHAMI KONSEP MATEMATIKA PADA MATERI KUBUS DAN BALOK - Albar Hidayat; Nenny Indrawati; Aprisal Aprisal (Program Studi Pendidikan Matematika, 2022)
This study aims to identify errors and factors that cause students' errors in the understanding concept of cubes and blocks. The subjects of this study were students of class VIII in SMPN 2 Pangale as many as 31 students. The study subjects were chosen to represent the students' ability levels, namely high, medium, and low categories. The instruments in this study were concept understanding tests and interview guidelines. Data analysis techniques used in this study include data reduction, data presentation, and drawing conclusions. The results of data analysis showed that students' errors in solving cube and block problems were in the medium category. Types of errors and factors that cause students to understand the concept of cubes and blocks are error in understanding the meaning of the problem and error in using the concept of the variable used. which contains (reading errors and errors in understanding the problem), incorrectly writing the formula, error in using theorem or definition to solve the problem, and not answering the question so that there is no solution to the problem or an error in writing the answer. The factors are preconceptions or students' initial concepts, student learning interests, student abilities, and context.